WALI MAJDZUBDALAM AL-QUR’AN: SEBUAH TINJAUAN SUFISTIK - Abd. Basid; Sabilil Maula (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
Wali majdzub is a servant who has been immersed in longing and full love for Allah SWT, he behaves strangely and looks shabby like a madman, but on the side of God he is his lover. The term majdzub itself comes from the world of Sufism. The origin of the word majdzub is jadzaba which means interesting. However, studies on this majdzub guardian are still minimal. This paper aims to analyze the truth of the wali Allah majdzub in the Qur'an from the perspective of Sufi scholars. With descriptive qualitative analysis method, this research article seeks to examine and examine how the wali majdzub in the Qur’an according to the views of Sufi scholars. 3:74. That wali majdzub is the level of guardianship that Allah bestows on his servants based on his will, without having someone take the path of suluk (way of worship). The truth of the guardian of majdzub is also strengthened by the opinions of Sufi scholars in their books.